A Study of Patient Preferences for the Treatment of Non–small Cell Lung Cancer in Western China: A Discrete-Choice Experiment - Liu, Fei; Hu, Haiyao; Wang, Jing; Chen, Yingyao; Hui, Sun; Hu, Ming (Frontiers in Public Health, 2021)
Background: Non–small cell lung cancer (NSCLC) is the most common histologic type of lung cancer, accounting for 70-85% of all lung cancers. Patients have differing preferences for treatment because of their varying physical conditions and socioeconomic backgrounds, which ultimately affects the choice of treatment as well as treatment outcomes. Objectives: The aim of this study was to elicit patient with Non–small cell lung cancer (NSCLC) preferences for treatment using a discrete-choice experiment and to explore the value/importance that patients place on the different attributes of treatment in order to provide a basis for clinical decision making and patient health management. Methods: The study was conducted with NSCLC patients in southwestern China. A discrete-choice experiment (DCE) including seven patient-relevant attributes was conducted using a fractional factorial SAS design. The empiric data analyses of patients were performed using mixed logit models. Results: 202 NSCLC patients completed the survey. Among the seven attributes, the following were considered important: progression-free survival, disease control rate, cost, weakness/fatigue, and nausea/vomiting; mode of administration and rash were considered less important. A clear preference for an increase in progression-free survival and disease control rate was demonstrated. Conclusions: This study demonstrates the value of DCEs in determining patient preferences for the treatment of NSCLC. The results indicate that not only efficacy factors were considered but also other factors (such as side effects and treatment costs) and trade-offs between attributes were held to be important.